Probing the Nature of Single-Photon Emitters in a WSe2 Monolayer by Magneto-Photoluminescence Spectroscopy - de Brito, Caique Serati; Rosa, Bárbara L. T.; Chaves, Andrey; Cavalini, Camila; Rabahi, César R.; Franco, Douglas F. [UNESP]; Nalin, Marcelo [UNESP]; Barcelos, Ingrid D.; Reitzenstein, Stephan; Gobato, Yara Galvão (American Chemical Society (ACS), 2024)
Monolayer transition metal dichalcogenides (TMDs) have emerged as promising materials to generate single-photon emitters (SPEs). While there are several previous reports in the literature about TMD-based SPEs, the precise nature of the excitonic states involved in them is still under debate. Here, we use magneto-optical techniques under in-plane and out-of-plane magnetic fields to investigate the nature of SPEs in WSe2 monolayers on glass substrates under different strain profiles. Our results reveal important changes on the exciton localization and, consequently, on the optical properties of SPEs. Remarkably, we observe an anomalous PL energy redshift with no significant changes of photoluminescence (PL) intensity under an in-plane magnetic field. We present a model to explain this redshift based on intervalley defect excitons under a parallel magnetic field. Overall, our results offer important insights into the nature of SPEs in TMDs, which are valuable for future applications in quantum technologies.